1993
DOI: 10.1126/science.8493574
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the von Hippel-Lindau Disease Tumor Suppressor Gene

Abstract: A gene discovered by positional cloning has been identified as the von Hippel-Lindau (VHL) disease tumor suppressor gene. A restriction fragment encompassing the gene showed rearrangements in 28 of 221 VHL kindreds. Eighteen of these rearrangements were due to deletions in the candidate gene, including three large nonoverlapping deletions. Intragenic mutations were detected in cell lines derived from VHL patients and from sporadic renal cell carcinomas. The VHL gene is evolutionarily conserved and encodes two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
1,384
2
44

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 2,642 publications
(1,470 citation statements)
references
References 31 publications
16
1,384
2
44
Order By: Relevance
“…The response of metastatic RCC to conventional chemotherapy is poor, but characterisation of the molecular pathology of RCC can provide a basis for developing novel therapeutic approaches. This is exemplified by the VHL TSG paradigm in which (a) inactivation of VHL is the most common event in sporadic clear cell RCC (Latif et al, 1993;Foster et al, 1994;Herman et al, 1994;Clifford et al, 1998); (b) VHL inactivation leads to stabilisation of HIF-1 and HIF-2 transcription factors and activation of hypoxic response genes that drive renal tumourigenesis (Maxwell et al, 1999); and (c) inhibitors (for example, tyrosine kinase inhibitors such as sorafenib and sunitinib) of HIF target pathways are active in the treatment of metastatic RCC (Chowdhury et al, 2008). Hence, identification of frequently inactivated RCC TSGs can provide a basis for novel therapeutic interventions.…”
Section: Ct Bstu1mentioning
confidence: 99%
“…The response of metastatic RCC to conventional chemotherapy is poor, but characterisation of the molecular pathology of RCC can provide a basis for developing novel therapeutic approaches. This is exemplified by the VHL TSG paradigm in which (a) inactivation of VHL is the most common event in sporadic clear cell RCC (Latif et al, 1993;Foster et al, 1994;Herman et al, 1994;Clifford et al, 1998); (b) VHL inactivation leads to stabilisation of HIF-1 and HIF-2 transcription factors and activation of hypoxic response genes that drive renal tumourigenesis (Maxwell et al, 1999); and (c) inhibitors (for example, tyrosine kinase inhibitors such as sorafenib and sunitinib) of HIF target pathways are active in the treatment of metastatic RCC (Chowdhury et al, 2008). Hence, identification of frequently inactivated RCC TSGs can provide a basis for novel therapeutic interventions.…”
Section: Ct Bstu1mentioning
confidence: 99%
“…Anomalies within the p53 tumor suppressor gene are not common in RCC. Mutations in the Von Hippel-Lindau (VHL) tumor-suppressor gene (Latif et al, 1993;Herman et al, 1994;Iliopoulos et al, 1995) or amplification and activation of the tyrosine kinase c-Met (Schmidt et al, 1997;Fischer et al, 1998;Zhuang et al, 1998;Lubensky et al, 1999) have been shown to play critical roles in the development of some RCCs. Despite these advances, the full spectrum of molecular changes that occur in the tumor is far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…Wilms tumor, also known as nephroblastoma, mostly affects children (Rivera and Haber, 2005). The majority of renal tumors occur sporadically, but a minority (B2%) of cases are associated with hereditary renal cancer diseases, such as the von Hippel-Lindau (VHL) syndrome (Latif et al, 1993), the hereditary papillary renal cancer (HPRC) syndrome (Schmidt et al, 1997), the hereditary leiomyomatosis and renal cell cancer (HLRCC) syndrome (Tomlinson et al, 2002) and the Birt-Hogg-Dube´(BHD) syndrome (Nickerson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%